Freedom of speech & the internet - Mokhtar, Khairil Azmin (2008)
The internet is a medium for individuals to exercise their freedom of speech. The internet, which has been referred as the information super highway, have significant role in many areas such as shaping public opinion and disseminating information. The effectiveness of the Internet as a medium of mass communication is no longer in doubt. The technology available today has created many Internet based services including blogs, chat rooms, instant messaging, news bulletins and virtual libraries. The convergence of traditional forms of broadcasting, telecommunications and online activities and services unsurprisingly gives rise to the question among policy makers in government as to whether there should be more effective means of regulation of the Internet. However the regulation run counter the idea of freedom of speech. This paper seeks to observe the scope of freedom of speech and certain types of content which seeks to be regulated and prohibited.